Program Pengembangan Nuklir Iran dan Pengaruhnya terhadap Masyarakat Iran (1957-2006 M) - Kiki Mikail; Achmad Fatoni (Universitas Islam Negeri Raden Fatah Palembang, 2019)
This research explain a series of developments related Iran's nuclear program that can cause conflict and displeasure particularly when Iran face the westrn country. The research takes two main problems,including the history of the emergence of Iran's nuclear program, and how the dynamics of Iran's nuclear development and the response of Middle Eastern countries. The results of the research that the history of the emergence of Iran's nuclear program in 1957 and in it is collaboration between Mohammad Shah Reza Pahlavi and the United States when Dwight D. Eisenhower become USA president. Then the Iraq-Iran war could affect the spirit to continue Iran's nuclear program. Furthermore, Rasfanjani has focused to the Iranian people welfare and emphasized his nuclear interests to become a fowerfull country and to protect iran country. however, Iran sanctioned by the United States which makes it difficult for Iran to export oil and gas.